Matières à produire l’espace. Une histoire environnementale des grandes infrastructures depuis 1945 - Nelo Magalhães (Revue de la Régulation)
This thesis focuses on the accumulation of material stocks, perceived as a production of space, in France since 1945. This process is studied through an environmental history of large-scale infrastructures. By examining their material flows, and by multiplying the points of view (from soils, laboratories, worksites, or quarries), we show that it is synonymous with Capitalocene, extractivism, disembedding, industrialization, and waste recovery. The production of space is as much about the stabilization, maintenance, upkeep, and extension of existing stocks as of new constructions. The chapters highlight the permanent attention and the substantial investments (monetary, technical, cognitive, and logistical) necessary to overcome the multiple crises and tensions that this production generates. It demands very particular landforms, the stability of soils and basements, an ideological work of naturalization of the built environment, and growing management and (economic and spatial) planning of extractive and waste spaces.